DRAGONFLIES INVENTORY (Odonata) IN KOTA WARINGIN VILLAGE, PUDING BESAR DISTRICT – BANGKA ISLAND - Pratama, Rahmat; Rosalini, Rega Alfi (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2016)
Odonata is considered an environmental indicator group of freshwater habitats. Thus there is a need to have a good baseline data to use it for monitoring fluvial habitats. However, species composition of Odonata in Kota Waringin Village is poorly known.This study aims to determine the diversity of dragonfly species in the Kota Waringin Village, Puding Besar District – Bangka Island. Data were collected at Three different ecosystems in Kota Waringin Village area (River in Forest, River in oil palm plantations and yard). Location for data collection based on the availability of water resources using purposive sampling method. The species were identified using identification books (Dragonfly of Singapore and Australian Dragonfly). Based on research we revealed 13 species of dragonflies are exist in three sampling locations (Agrionoptera insignis, Brachydiplax chalybea, Heliaeschna crassa, Ictinogomphus decoratus melaenops, Nannophya pygmaea, Neurothemis fluctuans, Neurothemis ramburii, Neurothemis terminata, Orthetrum chrysis, Orthetrum Sabina, Rhodothemis rufa, Zyxomma petiolatum and Rhyothemis phyllis). Keywords : Odonata, Dragonflies, Inventory, Conservation, Bangka Island